INTEGRATING AERODYNAMIC OPTIMIZATION AND SIMULATION TO ENHANCE UNMANNED ARIAL VEHICLE PERFORMANCE AND LOWER CARBON EMISSIONS - Yahya Zakaria; Mochamad Viky Afandy; Abiyu Ramadhan; Riduwan Prasetya; Yayi Febdia Pradani; Danang Yugo Pratomo; Misbachudin Misbachudin (Scientific Journal of Mechanical Engineering Kinematika, 2026)
This study develops an integrated aerodynamic optimization and simulation pipeline for fixed‑wing Unmanned Aerial Vehicle (UAV) to improve mission efficiency while projecting lower carbon emissions through energy use reductions. A parametric geometry with airfoil selection, aspect ratio, sweep, taper, twist, and winglet controls is optimized using a multi‑objective genetic algorithm coupled to Computational Fluid Dynamics (CFD) simulation. Objectives minimize drag and mission power while maximizing lift‑to‑drag under representative cruise conditions. A data‑efficient power model links aerodynamic states to per‑mission energy, enabling rapid iteration as a surrogate within the optimization loop. To ensure reliability, the CFD solver was validated against NASA experimental benchmarks for the NACA 0012 airfoil, achieving a margin of error below 3%. The optimization results demonstrate a significant shift from traditional baseline designs. By adopting a non-symmetric air foil combination, NACA 4412 root and NACA 2412 tip, increasing the aspect ratio to 9.8, and implementing specific winglet cant angels, the optimized design achieved a 44.7% reduction in aerodynamic drag. Visual analysis through velocity and pressure contours confirmed cleaner flow fields and weakened wingtip vortices, which directly translate to lower propulsion power. Ultimately, this study delivers a reproducible design pipeline an a Pareto-optimal map for balancing aerodynamic efficiency with structural practicality. While emissions were not measured directly, the documented 44.7% reduction in drag and corresponding decrease in energy demand provide a strong indicator for the potential to lower the carbon footprint of future UAV operations.